Tetrazine derived mononuclear Ru-II(acac)(2)(L)(1), [Ru-II(bpy)(2)(L)](ClO4)(2)(2) and [Ru-II(bpy)(L)(2)](ClO4)(2)(3) (L=3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate, bpy=2,2 '-bipyridine): syntheses, structures, spectra - Nayak, A.; Patra, S.; Sarkar, B.; Ghumaan, Sandeep; Puranik, Vedavati G.; Kaim, Wolfgang; Lahiri, Goutam Kumar (Polyhedron, 2005)
Mononuclear ruthenium complexes of tetrazine derived L, Ru-II(acac)(2)(L) (1), [Ru-II(bpy)(2)(L)](ClO4)(2) (2) and [Ru-II(bpy)(L)(2)](ClO4)2 (3) (L = 3-amino-6-(3,5-dimethylpyrazol-1-yl)-1,2,4,5-tetrazine, acac = acetylacetonate and bpy = 2,2'-bipyridine) were prepared. The free L exists as a dimeric entity in the solid state via hydrogen bonding interactions involving L and water molecules present in the crystal lattice. 1 exhibits unusually strong bonds from Ru-II to coordinating pyrazolyl-N (2.040(2) Angstrom) and especially to tetrazine-N (1.913(2) Angstrom). The Ru-III/Ru-II couples of 1-3 appeared at 0.28, 1.34 and 1.50 V versus SCE, respectively. The tetrazine and bpy-based reductions were observed at -1.33 (1); -0.55 and -1.55/-1.75/-1.98 (2); -0.47/-0.78 and -1.80/-2.02 V (3), respectively. 1, 2 and 3 displayed two MLCT bands each, corresponding to dpi(Ru-II) --> pi* (L, tetrazine) and dpi(Ru-II) --> pi* (acac or bpy or L) transitions. 1(+) and 2(+) showed rhombic EPR spectra at 110 and 4 K, respectively and 1(-), 2(-) and 3(-) exhibited multiple line EPR spectra at 300 K. 1-3 exhibited moderately strong emission spectra in EtOH-MeOH glass at 77 K. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Electrochemistry; redox; ruthenium-tetrazine; spectra; structure; synthesis

Mechanistic aspects of wet and dry CO oxidation on Co3O4 nanorod surfaces: a NAP-UPS study - Ruchi Jain; Gnanakumar, Edwin S.; Gopinath, Chinnakonda S. (ACS Omega, 2017)
Catalytic activity, electronic structure, and the mechanistic aspects of Co3O4 nanorod (NR) surfaces have been explored for CO oxidation in dry and wet atmosphere using near-ambient pressure ultraviolet photoelectron spectroscopy. Presence of water with CO + O2 plummets the catalytic activity because of the change in the electronic nature from predominantly oxide (without water in feed) to a Co3O4 surface covered by a few intermediates. However, at ≥375 K, the Co3O4 surface recovers and regains the oxidation activity, at least partially, even in the presence of water. This is fully supported by the changes observed in the work function of Co3O4 under wet (H2O + CO + O2) conditions compared with dry (CO + O2) conditions. This study focuses on the comparative CO oxidation rate on Co3O4 NR surfaces and highlights the changes in the electronic structure that occur in the catalyst during the CO oxidation reaction.
Keywords: Catalyst; Nano Structures; Power X-Ray Diffraction; spectra; Water Vapor

Nature of selenium hydrogen bonding: gas phase spectroscopy and quantum chemistry calculations - Mishra, Kamal K.; Singh, Santosh K.; Ghosh, Paulami; Ghosh, Debashree; Das, Aloke (Physical chemistry Chemical physics, 2017)
<div class="block-record-info" style="margin: 0px 22px 22px; list-style: none; padding: 0px; line-height: 20px; font-size: 13px; color: rgb(51, 51, 51); font-family: arial, helvetica, sans-serif; background-color: rgb(248, 248, 248);"> Subsequent to the recent re-definition of hydrogen bonding by the IUPAC committee, there has been a growing search for finding the presence of this ever interesting non-covalent interaction between a hydrogen atom in an X-H group and any other atom in the periodic table. In recent gas phase experiments, it has been observed that hydrogen bonding interactions involving S and Se are of similar strength to those with an O atom. However, there is no clear explanation for the unusual strength of this interaction in the case of hydrogen bond acceptors which are not conventional electronegative atoms. In this work, we have explored the nature of Se hydrogen bonding by studying indole...dimethyl selenide (indmse) and phenol...dimethyl selenide (phdmse) complexes using gas phase IR spectroscopy and quantum chemistry calculations. We have found through various energy decomposition analysis (EDA) methods and natural bond orbital (NBO) calculations that, along with electrostatics and polarization, charge transfer interactions are important to understand Se/S hydrogen bonding and there is a delicate balance between the various interactions that plays the crucial role rather than a single component of the interaction energy. An in-depth understanding of this type of non-covalent interaction has immense significance in biology as amino acids containing S and Se are widely present in proteins and hence hydrogen bonding interactions involving S and Se atoms contribute to the folding of proteins.
Keywords: Center-Dot-O; Clusters; Co-Ordination; Complexes; intermolecular interactions; Proteins; Replacement; spectra; Strength; Sulfur

Nutty carbon: morphology replicating hard carbon from walnut shell for na ion battery anode - Wahid, M.; Gawli, Y.; Puthusseri, D.; Kumar, A.; Shelke, M. V.; Ogale, S. (ACS Omega, 2017)
<div id="absImg" style="position: relative; margin: 0px; padding: 5px; border: 1px solid rgb(204, 204, 204); border-radius: 5px; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial; text-align: center; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;"><img alt="Abstract Image" src="http://pubs.acs.org/appl/literatum/publisher/achs/journals/content/acsodf/2017/acsodf.2017.2.issue-7/acsomega.7b00633/20170713/images/medium/ao-2017-00633k_0006.gif" style="border: 0px; max-width: 100%;"> <p class="articleBody_abstractText" style="margin: 0px 0px 1.5em; line-height: 1.6em; padding: 0pt; width: 610px; word-wrap: break-word; color: rgb(0, 0, 0); font-family: Helvetica, Arial, sans-serif; font-size: 14px;">Efficient Na ion intercalation/deintercalation in the semigraphitic lattice of a hard carbon derived from the walnut shell is demonstrated. High-temperature (1000 °C) pyrolysis of walnut shells under an inert atmosphere yields a hard carbon with a low surface area (59 m2 g–1) and a large interplanar c axis separation of 0.39–0.36 nm as compared to 0.32 nm for graphite, suitable for Na ion intercalation/deintercalation. A stable reversible capacity of 257 mAh g–1 is observed at a current density of 50 mA g–1 for such nutshell-derived carbon (NDC) with an impressive rate performance. No loss of electrochemical performance is observed for high current cycling (100 mA g–1 → 2 A g–1 → 100 mA g–1). Additionally, the NDC shows remarkably stable electrochemical performance up to 300 charge–discharge cycles at 100 mA g–1 with a minimal drop in capacity.
Keywords: Batteries; Biological and Medicinal chemistry; Biological materials; diffraction; Electric Properties; Electrode-electrolyte interface; spectra; Surface structure; Thermal properties